PERKEMBANGAN SISTEM PEMBAYARAN DIGITAL PADA ERA REVOLUSI INDUSTRI 4.0 DI INDONESIA - Jefry Tarantang; Annisa Awwaliyah; Maulidia Astuti; Meidinah Munawaroh (AL-QARDH, 2019)
In line with the rapid development of technology, patterns and payment systems in economic transactions continue to change. Technological advances in the payment system are shifting the role of cash (currency) as a means of payment in the form of digital payments that are more efficient and economical. In its development, several countries have discovered and used electronic payment products known as Electronic Money (e-money). The presence of non-cash payment instruments mentioned above, is not only caused by innovations in the banking sector but also driven by the public's need for practical payment instruments that can provide convenience in conducting transactions. This paper aims to analyze the impact of the development of digital payment systems on the existence of cash in the era of the digital economy. In addition, this also minimizes the risks that can be caused by the use of digital payment systems and prevents inflation due to the large amount of cash in circulation. The method used in this paper is qualitative and is supported by a phenomenological approach. The results of this study indicate that technological advancements in the era of the digital economy (Industrial Revolution 4.0) are indeed unavoidable, especially in the rapid development of digital payment systems. Digital payment systems have advantages and disadvantages. But in general, the advantages of digital payment systems outweigh the disadvantages. The presence of this digital payment system does not mean eliminating the existence of cash. However, the existence of a digital payment system can also minimize the occurrence of inflation due to the large amount of money circulating in the community.